INFLUENCE OF MASSOTHERAPY (BABY SQUEEZE) AND SIDE DISH GIVING TO GIZI STATUS OF BALITA AGE 1-3 YEAR WITHGIZILESS - Sajidin, Muhammad; Kusumawati, Wanda (JURNAL KEPERAWATAN BINA SEHAT, 2012)
Balita period represent quickly phase of brain grow which in its growth need good gizi in order to be able to grow in an optimal one. That thing earn to be strived by doing massotherapy (baby squeeze) and side dish giving routinely. The aim of this research is to analyse influence of massotherapy (baby squeeze) and side dish gizi to gizi status of balita age 1-3 year with giziless on orchard jogodayoh orchard Jabon village. Design of this research is a pre experiment of one group pre test-post test design. Population are 140 balita and technique of probability type simple random sampling got sampel as many as 10 balita. Independent variable is influence of massotherapy (baby squeeze) and side dish giving and dependent variable is gizi status of balita age 1-3 year. Data collected with questioner, observation and numeration with antropometri formula before and after masssotherapy (baby squeeze) and side dish giving on 4 May - 2 June 2011. Data analysis by using Wilcoxon Sign Rank Test. Result of research show there are analyse influence of massotherapy (baby squeeze) and side dish gizi to gizi status of balita age 1-3 year with giziless on orchard jogodayoh orchard Jabon village with ρ( 0,003)< α( 0,05). Balita gizi status relate to food, disease, food resilience, pattern mothering of child, health services and environment health. Health offficer can assist to instruct mother apply massotherapy (baby squeeze) and side dish giving to take care of balita gizi status in good condition level. Mother who have balita with status of giziless expected to persist massotherapy (baby squeeze) and side dish giving to increase gizi status of their balita while mother who have balita with gizi status in good level can persist massotherapy (baby squeeze) and side dish giving routinely to prevent the happening gizi balita problem.Keyword: massotherapy (baby squeeze), side dish giving